Improving Student Social Interaction Through Group Counseling Using the Rational Emotive Behavior Therapy Approach - habibi, ahmad ali habibi sitompul (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to improve students' social interaction through group counseling using the Rational Emotive Behavior Therapy (REBT) approach. This study uses the Classroom Action Research method, which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The research subjects were students at SMP Negeri 5 Percut Sei Tuan who exhibited low levels of social interaction, such as reluctance to communicate, difficulty collaborating, and limitations in self-expression. Data were analyzed using percentage formulas and qualitative descriptions. The results of the study showed an improvement in students' social interaction skills after participating in two cycles of group counseling. Students became more confident, open in expressing their feelings, and active in discussions and group cooperation. These findings indicate that the REBT approach is effective when applied in group counseling to support positive behavioral change and improve students' social interaction in the school environment.